The Genus of Tangle Closures - Litzau, Kathryn (My University, 2013)
The purpose of this study was to develop an understanding of rational tangles and their relationship to genus.
Color poster with text, diagrams, and tables.
Keywords: Seifert's algorithm; Knot theory; Posters